DOPANT ELEMENT TO ACHIEVE HIGH IONIC CONDUCTIVITY IN LI7LA3ZR2O12 SOLID ELECTROLYTE IN LITHIUM ION BATTERIES - Hanif Hawari, Naufal
Batteries, such as Li-ion batteries are an energy storage device which is needed to ensure the wide application of sustainable energy harvesting technology. Several drawbacks still limit the performance of li-ion batteries, such as the flammability of the organic electrolyte and low capacity of the batteries. In general, lithium ion batteries use a cathode made of LiFePO4 (LFP) due to its good safety and acceptable capacity. The galvanostatic charge-discharge test for 5 cycles using 0,20 of C-rates revealed that the LFP coin cell showed an initial colombic efficiency of 72,13%, discharge capacity of 104,87 mAh / g, and a capacity retention of 94.55%. The low initial colombic efficiency was attributed to the formation of solid electrolyte interphase (SEI) on the anode of lithium ion battery. Inorganic solid electrolytes such as NASICON Li1,3Ti1,7Al0,3(PO4)3 (LATP) and garnet oxide Li7La3Zr2O12 (LLZO) were used to overcome the proposed problem. LATP sample showed a low ionic conductivity (5,3 x 10-6 S / cm) due to the low relative density of the sample (61,13%). On the other hand, literature on cubic phase LLZO suggest a promising performance as a solid electrolyte. Incorporation of LLZO with Ga element (i.e. Ga-LLZO) provides the highest ionic conductivity (2.06 x 10-3 S / cm) and the lowest activation energy (0.22 eV). The promising properties of Ga-LLZO is a potential for further development of high capacity and safe lithium ion battery.